2006
DOI: 10.2337/diabetes.55.02.06.db05-1066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pioglitazone on Pancreatic β-Cell Function and Diabetes Risk in Hispanic Women With Prior Gestational Diabetes

Abstract: The Pioglitazone In Prevention Of Diabetes (PIPOD) study was conducted to evaluate ␤-cell function, insulin resistance, and the incidence of diabetes during treatment with pioglitazone in Hispanic women with prior gestational diabetes who had completed participation in the Troglitazone In Prevention Of Diabetes (TRIPOD) study. Women who completed the TRIPOD study were offered participation in the PIPOD study for a planned 3 years of drug treatment and 6 months of postdrug washout. Oral glucose tolerance tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
279
3
11

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(305 citation statements)
references
References 20 publications
12
279
3
11
Order By: Relevance
“…This was in contrast to reports that pioglitazone [9], troglitazone [6,8] and rosiglitazone [7] are highly effective preventive agents in different populations. Troglitazone was found to be highly effective in reducing the incidence of diabetes in individuals with IGT [6] and in women with a history of GDM [8], but these studies had to be terminated prematurely because of hepatic toxicity of the drug.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This was in contrast to reports that pioglitazone [9], troglitazone [6,8] and rosiglitazone [7] are highly effective preventive agents in different populations. Troglitazone was found to be highly effective in reducing the incidence of diabetes in individuals with IGT [6] and in women with a history of GDM [8], but these studies had to be terminated prematurely because of hepatic toxicity of the drug.…”
Section: Discussioncontrasting
confidence: 92%
“…Insulin sensitisers such as metformin [3,4] and the glitazones [6,7] have also been useful in the primary prevention of diabetes in people with IGT and in women with a history of gestational diabetes (GDM) [8,9], in different ethnic groups. Results of the Actos Now for Prevention of Diabetes (ACT NOW) study, presented in the 68th Annual Meeting of the American Diabetes Association in June 2008, showed that pioglitazone produced a remarkable reduction (81%) in conversion of IGT to diabetes in a mean period of 2.6 years, in the US population [10].…”
Section: Introductionmentioning
confidence: 99%
“…Women with a history of GDM also constitute a high-risk population. Women who developed GDM and were treated with pioglitazone in the Pioglitazone in Prevention of Diabetes study had stable pancreatic b-cell function and a relatively low subsequent incidence of diabetes [10].…”
Section: # 2008 Published By Elsevier Ireland Ltdmentioning
confidence: 99%
“…DI values of 2,000 and above are typical of subjects with normal glucose tolerance while DI values under 1,000 have been reported in populations at high risk for type 2 diabetes, such as Hispanic women with prior gestational diabetes. 24 In the sleep debt condition, the DI was 40% lower than after sleep recovery and 3 of the 11 subjects had DI values under 1,000. Table 2 compares the glucose tolerance (K G ) values observed in these healthy young men at the end of the sleep debt condition and when fully rested to values obtained in different subject populations using the same ivGTT protocol and mathematical analysis.…”
Section: Laboratory Studies Of Glucose Metabolism and Sleep Lossmentioning
confidence: 99%